SEPA+PrEP-BW intervention: A feasible and acceptable HIV prevention intervention for Black women - Rosina Cianelli; Joseph P. De Santis; Evelyn Iriarte; Giovanna C. De Oliveira; Renessa Williams; Regine Placide Reaves; José G. Castro; Shanelle Hodge; Sophia O. Thomas; Carolyn Edwards; María José Baeza Robba; Natalia Villegas; et al. (PLoS ONE, 2025)
Although biomedical prevention strategies such as Pre-Exposure Prophylaxis (PrEP) are available, Black women (BW), who comprise less than 15% of the female population in the United States, account for 54% of new HIV infections among women. Many BW underestimate their HIV risk and face barriers to prevention, including traditional gender roles, racism, stigma, and medical mistrust. To address these challenges, we adapted SEPA+PrEP into SEPA+PrEP-BW, a novel biobehavioral HIV prevention intervention that integrates the empirically validated SEPA model (Salud/Health, Educación/Education, Prevención/Prevention, Autocuidado/Self-Care) with PrEP education and culturally relevant components tailored to BW. Using a mixed methods approach, we collected and analyzed quantitative and qualitative data from 73 BW residing in Miami-Dade County, Florida. Results demonstrated high feasibility (94.5% retention rate), strong acceptability (94.2% satisfaction with content), and unanimous willingness to recommend the intervention. Participants expressed interest in becoming peer facilitators and emphasized the importance of culturally relevant education and safe spaces for discussion. These findings support SEPA+PrEP-BW as a promising, community-driven intervention to address critical gaps in HIV prevention among BW.